Risk factors and locations of falls among older pilgrims during Hajj: Implications for targeted prevention - Walid A. Alkeridy; Khulud K. Alharbi; Shahad M. Sofi; Bashaier D. Alosaimi; Abrar M. Aljohani; Basmah A. Rafie; Bashaier A. Fairaq; Gehan K. Mubaraki; Nawal A. Sindi; Maha M. Almarwani (Journal of Infection and Public Health, 2025)
Falls are a major cause of morbidity and mortality among older adults, with risks heightened during physically demanding mass gatherings such as the Islamic Hajj. However, research addressing fall-related risks during Hajj remains limited. This study aimed to determine the prevalence, risk factors, and common locations of falls among older pilgrims. A cross-sectional survey was conducted during the 2024 Hajj among pilgrims aged ≥60 years. Data were collected through structured interviews using standardized questionnaires on demographics, medical history, fall occurrence, locations, and injuries. Logistic regression was used to identify independent predictors. Among 777 participants (median age 68.0 years; 60.2 % male), 39 (5.0 %) reported falls. Most occurred at high-density sites, especially Mena (46.2 %), followed by the Grand Mosque and Arafat (each 17.9 %). Falls occurred during the throwing of Jamarat, in bathrooms, and on stairs. Non-Saudi nationality (OR = 2.53, p = 0.010) and asthma (OR = 3.78, p = 0.005) were identified as independent predictors. Injuries occurred in 28.2 % of fallers, and 23.1 % required emergency care. Targeted interventions are essential, including pre-travel assessments, multilingual educational programs, improved infrastructure, and designated walking paths. Future studies should explore the feasibility of real-time surveillance systems to enhance fall detection and safety during Hajj.